Price competition and reputation in credence goods markets: Experimental evidence - Wanda Mimra; Alexander Rasch; Christian Waibel (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
In credence goods markets, experts have better information about the appropriate quality of treatment than their customers. As experts provide both diagnosis and treatment, this leaves scope for fraud. We experimentally investigate how intensity of price competition and the level of customer information about past expert behavior influence an expert's incentive to defraud his customers when the expert can build up reputation. We show that the level of fraud is significantly higher under price competition than when prices are fixed. The price decline under competitive prices superimposes quality competition. More customer information does not necessarily decrease the level of fraud.
Keywords: D82; L15; 330; Credence good; Expert; Fraud; Price competition; Reputation; Overcharging; Undertreatment; Vertrauensgüter; Preiswettbewerb; Reputation; Anreiz; Betrug; Theorie